A Plastic Injection Molding Process Characterisation Using Experimental Technique: A Case Study - Mohamed Yusoff, Shaik Mohamed; Mohd. Rohani, Jafri; Wan Hamid, Wan Harun; Ramly, Edly (Penerbit UTM Press, 2004)

(untitled)
This Paper Illustrates An Application Of Design Of Experimental (DOE) Approach In An Industrial Setting For Identifying The Critical Factors Affecting A Plastic Injection Molding Process Of A Certain Component For Aircond Assembly. A Critical To Quality (CTQ) Of Interest Is Reducing Process Defects, Namely Short-Shot. A Full Factorial Design Was Employed To Study Simultaneously The Effect Of Five Injection Molding Process Parameters. The Five Process Parameters Are Backpressure, Screw Rotation Speed, Spear Temperature, Manifold Temperature, And Holding Pressure Transfer. Finally, The Significant Process Parameters Influencing The Short-Shot Defect Have Been Found. Empirical Relationship Between CTQ And The Significant Process Parameters Were Formulated Using Regression Analysis.